ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA KELAS IV SDN KENDALREJO 01 TAHUN PELAJARAN 2017/2018 - fajrin, ria (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2018)
Mathematics is one of the main subjects taught starting from elementary school level. Most students do not like math lessons, resulting in low learning outcomes. This study aims to (1) Describe the types of difficulties experienced by students in solving the story problems in grade 4 students of SDN Kendalrejo 01, and (2) Knowing and describing what factors cause students having difficulty in solving the story problem in the students grade IV SDN Kendalrejo 01.               Research method using qualitative research type with case study approach. Data obtained from the results of mathematical tests materisoal stories, data hadil observation, and data interviews. For the data source used all students of class IV SDN Kendalrejo 01 which amounted to 21 students. The instruments used in the research are test, observation, and interview.               The result of the research shows the factors that cause the students having difficulties in solving the matrix problems include internal factors and external factors. Internal factors, (1) Students are less able to understand each question in the test questions so that the answers from students deviate from the questions that have been asked, (2) Students assume that math is the most difficult lesson so that students are lazy to think and thoroughly in doing the problem, in adding or subtracting in the concept of story, (3) Students feel less able to focus every problem in the lesson, focus on listening when the teacher explains, not paying attention when the teacher writes on the board so that students will find it difficult after giving them the problem to do it yourself. External factors, (1) Teachers are too patient to be less appropriate with the expected students, (2) The class situation is noisy due to the lack of student responses during the learning process, (3) Teachers are less able to understand what students want in the learning process in the classroom, (4) lack of spirit of learning and encouragement from parents at home to learn, (5) too much time playing outside so less time to learn.